Harmonisasi Keragaman dalam Komunitas Meditasi Kesadaran di Wihara Mendut - Waluyo Waluyo (Jurnal Pelita Dharma, 2019)
This study aims to describe harmony in the diversity of the Awareness Meditation community at the Mendut Temple. This study uses a qualitative case study model approach. The subjects of the study are participants in the Awareness Meditation retreat held at Mendut Temple, Magelang. The object of the study is the diversity of the retreat participants' spiritual orientations which were explained in three themes namely the relevance of meditation to the problems of life, their impact on participants, and the meaning of diversity in the Awareness Meditation community. Data collection used non-test technique through observation, interviews, and documentation with observation guidance instruments, interview guidelines, and other supporting documents. The validity of the data uses a test of credibility, transferability, dependability, and confirmability. Data were analyzed using the Miles Huberman model. The results showed that: (a) the relevance of meditation with problems of life for participants in the retreat of awareness meditation at the Mendut Temple is closely related to the participant introduction to meditation, interpersonal comparisons, search stages, ability to identify life problems and problems in attending mindfulness meditation, and suggestions for organizers in supporting the implementation of meditation; (b) the impact of meditation on daily life for retreat participants includes the form of the exercise, the training schedule and time, how to respond to the situation, a higher understanding of mindfulness meditation, the requirements of the practice, the meaning of the impact on participants, and the results of meditation; and (c) the views of the participants of the mindfulness meditation retreat have a close relationship with observance of participating in the retreat, the relationship of fellow participants, the perspective of other religions, the nature of diversity, and the sustainability of the community in the future. Penelitian ini bertujuan untuk mendeskripsikan keharmonisan dalam keragaman komunitas Meditasi Kesadaran di Wihara Mendut. Penelitian ini menggunakan pendekatan kualitatif model case study. Subjek penelitian adalah peserta retret Meditasi Kesadaran yang dilaksanakan di Wihara Mendut, Magelang. Objek penelitian adalah keragaman orientasi spiritual peserta retret yang dijelaskan dalam tiga tema yaitu relevansi meditasi dengan permasalahan kehidupan, dampaknya bagi peserta, dan makna keberagaman dalam komunitas Meditasi Kesadaran. Teknik pengumpulan data menggunakan nontes melalui observasi, wawancara, dan dokumentasi dengan instrumen pedoman observasi, pedoman wawancara, dan dokumen pendukung lainnya. Keabsahan data menggunakan uji kredibilitas, transferabilitas, dependabilitas, dan konfirmabilitas. Data dianalisis menggunakan model Miles Huberman. Hasil penelitian menunjukkan bahwa: (a) relevansi meditasi dengan permasalahan kehidupan bagi peserta retret meditasi kesadaran di Wihara Mendut berkaitan erat dengan permulaan peserta mengenal meditasi, perbandingan antarguru, tahapan pencarian, kemampuan mengidentifikasi permasalahan kehidupan dan problematika dalam mengikuti meditasi kesadaran, dan saran bagi penyelenggara dalam mendukung pelaksanaan meditasi; (b) dampak meditasi dalam kehidupan sehari-hari bagi peserta retret meliputi bentuk latihan, jadwal dan waktu latihan, cara menanggapi situasi, pemahaman yang lebih tinggi dalam meditasi kesadaran, persyaratan berlatih, makna dampak bagi peserta, dan hasil meditasi; dan (c) pandangan peserta retret meditasi kesadaranmemiliki kaitan erat dengan ketaatan dalam mengikuti retret, hubungan sesama peserta, cara pandang terhadap agama lain, hakikat keberagaman, dan keberlanjutan komunitas di masa mendatang.